Molecular Detection of Colistin Resistance Gene mcr-1 in Gram negative Rods Isolated from Hospitalized Patients in Khartoum Stat - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2020)
Background: The emergence of the plasmid-mediated mcr-1 colistin-resistance genes in bacteria poses a potential threat for treatment of patients, especially when hospitalized. The pinpoints of this study were to search for the presence of mcr 1genein the thick of gram negative rods (Eschericea coli, Klebsiella spieces, Pseudomonas speices, Proteus speices, Aceinetobacter species, Serritia and Citrobacter species) isolates from clinical specimen using Polymerase Chain Reaction (PCR) technique. Methods: In this study, 185 nonduplicate Enterobacteriaceae isolates from clinical specimens were tested. Antimicrobial susceptibility test on 11 antibiotics was done by Kirby baur disk diffusion method. The presence of mcr-1 gene was investigated by PCR technique. Results: Out of 185 non duplicate Enterobacteriaceae, 6 isolates show positive mcr-1 gene including one Isolate (16.4%) Pseudomonas aeurginosa from urine sample, and 5 (83.3%) Klebsiella pneumonia isolated from two wound sample (40%), one high vaginal swab sample (20%), one blood sample (20%) and one urine sample (20%). Most of Isolates that harboring mcr-1 gene detected by PCR isolated from patients were used antibiotics for treatment (n=4 (66.6%)). Conclusion: Colistin (Polymycin E) which used for treating Gram- negative bacterial infections should be mainly used for treating the severest infection to preserve their effectiveness and to avoid transferring of the gene from one bacterium to other by the different methods of genes transferring.